Metabolite analysis reveals flavonoids accumulation during flower development in Rhododendron pulchrum sweet (Ericaceae) - Yang, Qiaofeng; Li, Zhiliang; Ma, Yuting; Fang, Linchuan; Liu, Yan; Zhu, Xinyu; Dong, Hongjin; Wang, Shuzhen (PeerJ, 2024)
The azalea (Rhododendron simsii Planch.) is an important ornamental woody plant with various medicinal properties due to its phytochemical compositions and components. However little information on the metabolite variation during flower development in Rhododendron has been provided. In our study, a comparative analysis of the flavonoid profile was performed in Rhododendron pulchrum sweet at three stages of flower development, bud (stage 1), partially open flower (stage 2), and full bloom (stage 3). A total of 199 flavonoids, including flavone, flavonol, flavone C-glycosides, flavanone, anthocyanin, and isoflavone were identified. In hierarchical clustering analysis (HCA) and principal component analysis (PCA), the accumulation of flavonoids displayed a clear development stage variation. During flower development, 78 differential accumulated metabolites (DAMs) were identified, and most were enriched to higher levels at the full bloom stage. A total of 11 DAMs including flavone (chrysin, chrysoeriol O-glucuronic acid, and chrysoeriol O-hexosyl-O-pentoside), isoflavone (biochanin A), and flavonol (3,7-di-O-methyl quercetin and isorhamnetin) were significantly altered at three stages. In particular, 3,7-di-O-methyl quercetin was the top increased metabolite during flower development. Furthermore, integrative analyses of metabolomic and transcriptomic were conducted, revealing that the contents of isoflavone, biochanin A, glycitin, and prunetin were correlated with the expression of 2-hydroxyisoflavanone dehydratase (HIDH), which provide insight into the regulatory mechanism that controls isoflavone biosynthesis in R. pulchrum. This study will provide a new reference for increasing desired metabolites effectively by more accurate or appropriate genetic engineering strategies.
Keywords: Rhododendron pulchrum sweet; Flavonoids; Flower development; Flavonol; Isoflavone